How Much Do State-Owned Enterprises Contribute to China’s GDP and Employment? - Zhang, Chunlin (World Bank, Washington, DC, 2019)
A large sector of state-owned enterprises (SOEs) is well known as the hallmark of the Chinese economy. But exactly how much do they contribute to the country’s gross domestic product (GDP) and employment? Since available statistics do not provide a straightforward answer, this note attempts to make some estimations. In conclusion, estimations in this note suggest that the share of SOEs in China’s GDP should be twenty-three to twenty-eight percent and their share in employment can be anywhere between five and sixteen percent in 2017.